2012
DOI: 10.2174/157016212803901338
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of CYP2B6-516G>T Polymorphism with Plasma Efavirenz Concentration and Depression in HIV-Infected Adults in Northern Thailand

Abstract: The prevalence of CYP2B6-516G > T polymorphism in northern Thai population is high and strongly associated with inter-individual drug levels variation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Several studies have shown that SNPs in CYP2B6 -particularly 516G>T-are associated with high plasma concentrations of efavirenz and drug-related toxicity (Nyakutira et al, 2008, Ramachandran et al, 2009, Aurpibul et al, 2012. In addition, the CYP2B6 polymorphism 516G>T was shown to be associated with higher than expected concentrations of the intravenous anesthetic propofol (Mastrogianni et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that SNPs in CYP2B6 -particularly 516G>T-are associated with high plasma concentrations of efavirenz and drug-related toxicity (Nyakutira et al, 2008, Ramachandran et al, 2009, Aurpibul et al, 2012. In addition, the CYP2B6 polymorphism 516G>T was shown to be associated with higher than expected concentrations of the intravenous anesthetic propofol (Mastrogianni et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the variant Tallele associated with higher plasma concentration of the drug, it was associated with Nevirapine-induced cutaneous reaction, which was stronger with a combination of the genotype CYP2B6 516G T carriers with HLA-Cw*04 alleles [47,[71][72][73][74][75]. Identification of polymorphisms CYP2B6 516G > T, 983T > C, 785A > G and 21563C > T SNPs are associated with increased plasma concentrations of Efavirenz and the development of more severe CNS lesions in HIV-infected, as well as increased concentration of Efavirenz was associated with CYP2A6 -48T > G and homozygous GG for UGT2B7 735, SNP microsomal enzyme uridine 5-diphospho-glucuronosyl transferase (UGT) [76][77][78][79]. Regarding phenytoin, clinical supervision among Taiwanese, Japanese and Malaysian patients showed a strong Association with the allelic variant CYP2C9*3, which was associated with decreased activity of CYP2C9 by 90% [80].…”
Section: Immune Reactionmentioning
confidence: 97%
“…The CYP2B6 c.516G>T polymorphism was shown to modulate the TB therapeutic response (Fernandes et al, 2015). The CYP2B6 c.516G>T has been associated with an increased plasma exposure to EFV (Cortes et al, 2013;Sinxadi et al, 2015;Swart et al, 2013) and increased risk of toxicity in the CNS (Aurpibul et al, 2012;Martin et al, 2014;Sinxadi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%